Situation Report: Hungary, 21 June 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Imre Nagy Executed 25 Years Ago / by Judith Pataki Vatican Official in Hungary / by Alfred Reisch Catholic Church Presses for Greater Role in Society / by Alfred Reisch Private Theater Performance Stopped by Organized Claque / by Eva Lengyel Another Warning to Gyorgy Konrad / by Alfred Reisch A New Bread of Political Commissars in the Military? / by Eva Lengyel Greater Independence for the Postal Service / by Alfred Reisch Personnel Changes and Religious News / by Alfred Reisch